Transactions on computational science XVII - Gavrilova, Marina. ((Transactions on computational science, 2013)
The LNCS journal Transactions on Computational Science reflects recent developments in the field of Computational Science, conceiving the field not as a mere ancillary science but rather as an innovative approach supporting many other scientific disciplines. The journal focuses on original high-quality research in the realm of computational science in parallel and distributed environments, encompassing the facilitating theoretical foundations and the applications of large-scale computations and massive data processing. It addresses researchers and practitioners in areas ranging from aerospace to biochemistry, from electronics to geosciences, from mathematics to software architecture, presenting verifiable computational methods, findings, and solutions and enabling industrial users to apply techniques of leading-edge, large-scale, high performance computational methods. The 17th issue of the Transactions on Computational Science journal consists of two parts. The first part is comprised of four papers, spanning the areas of robotics and augmented reality, computer game evaluation strategies, cognitive perception in crowd control simulation, and reversible processor design using look-ahead. The second part consists of five papers  covering the topics of secure congestion adaptive routing, cryptographic schemes for wireless sensor networks, intersection attacks on anonymity, and reliable message delivery in Vehicular Ad Hoc Networks (VANET). An evaluation of camera Pose methods for an augmented reality system: application to teaching industrial robots -- A combined position evaluation function in chinese chess computer game -- Modeling and analyzing the human cognitive limits for perception in crowd simulation -- Progress in reversible processor design: a novel methodology for reversible carry look-ahead adder -- Secure congestion adaptive routing using group signature scheme -- Practicability of HFE scheme for wireless sensor network -- Intersection attack on anonymity in VANET -- Cluster based RSU centric channel access for VANETs -- Efficient identity-based and authenticated key agreement protocol.